If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -8) + 26 = 0 Reorder the terms: 5(-8 + x) + 26 = 0 (-8 * 5 + x * 5) + 26 = 0 (-40 + 5x) + 26 = 0 Reorder the terms: -40 + 26 + 5x = 0 Combine like terms: -40 + 26 = -14 -14 + 5x = 0 Solving -14 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 5x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 5x = 0 + 14 5x = 0 + 14 Combine like terms: 0 + 14 = 14 5x = 14 Divide each side by '5'. x = 2.8 Simplifying x = 2.8
| 5x-4(4x-1)=2 | | -6x-142=2x+98 | | 5x+45+9x=180 | | 17=64-n | | i7n/9-62=5n/9-49 | | 31x=56 | | Y/3-4=-2 | | B/5-2=2 | | 4+-6+9=x | | .10x+12y=2990 | | a/4-b/3=5/12 | | -2+5n+3n^2=0 | | 10=30/z | | 9p-19=5(p-2)-2(7-2p) | | 5v-5v+v=16 | | Y=-4(6)-10 | | (14-2x)+40=180 | | -2x-10=-2x-10 | | x-10y=13 | | 1=k/10-1 | | x^2-14x-40= | | (14-2x)+40=90 | | 12x+6y= | | 2(-6p+7)+4(p+3)= | | 3x^2-20x+25= | | 11d-4d-3d+d-4d=12 | | 23-4r=3 | | -48-3x=42+2x | | 6X9-/5X | | (14-2x)+40= | | 3(6+t)-1= | | 3(-5x-4)-2x=6 |